HOW DOES STRENGTHENING ISLAMIC BANKING COMPETITIVENESS? INDONESIA EVIDENCE - Budi Sukardi; Mohammad Albizar Putra Riyadi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2022)
The quality of service provided depends on the ability of service providers to meetcustomers’ expectations. This study aims to determine the impact of Islamic servicequality and floating market methods on the competitiveness of Islamic banks. Thisstudy used quantitative methods with non-probability sampling techniques, usingpurposive sampling techniques. The study population was BTN Syariah customers.The data acquisition was made by spreading questionnaires to customers. Informationgleaned from specific considerations tailored to the research’s purpose or problemand data analysed by multiple linear regression techniques. The results showed thatIslamic service quality affects the competitiveness of Islamic banks, and marketingmethods based on the floating market affect the competitiveness. The study improvedBTN Syariah Indonesia’s competitiveness in Islamic service quality and marketingmethods based on the floating market. This research helps banks recognise the pointsand strategies for strengthening Islamic banks’ competitiveness and generatingpositive experiences to gain customer loyalty with the proper approach, namelyIslamic service quality and marketing strategies with floating market methods.